Comparação entre misturas de extratos proteicos em aves com interesse comercial - Figueira, Paulo Tadeu [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
We see the growing consumer demand for meat foods, particularly those relating to features such as tenderness, juiciness and odor, which are directly related to the constitution of the protein product, together with the lipids and carbohydrates. In the current panorama of consumption of meat products in Brazil, the poultry origin show a significant increase, and the development of derivatives has followed this advance. In this sense, identify whether there is undue meats mixtures of by-products is vitally important. To assess the quality of the assessment of the origin and quality of muscle proteins is a major factor as well as the evaluation of protein losses during rigor mortis process. The main techniques for protein quantification are electrophoretic and densitometric. To evaluate the protein losses can still be used the histology of muscle tissues technique. For this work, he left that the muscle proteins of chickens and turkeys have different structural characteristics due to gene expression and their primary structures can be identified even in mixtures, by electrophoretic techniques, and through densitometry quantified. Pectoral muscle fragments poultry slaughtered were collected in the laboratory, in addition to the evaluation of protein extracts mixing, accomplish the evaluation of the loss occurred during the resolution of rigor mortis. The fragments obtained were evaluated for histological and electrophoretic technique, currents being collected at times 0, 30, 60, 90, 120 and 150 minutes after the slaughter. Protein extraction with another of the same fragments by maceration and centrifugation, and subsequent mixture of extracts in the proportion 80, 60, 40 and 20% yet been performed for later submission to IEF technique on Phast-Gel. The results showed that the protein loss in the resolution of rigor mortis were not significant, even with the total transformation of the tissue at post mortem. Furthermore, the protein mixtures...

Cada vez mais vemos o crescimento da exigência do consumidor para alimentos cárneos, principalmente as que se referem a características como maciez, a suculência e o odor, que estão diretamente ligadas a constituição proteica do produto, juntamente com os lipídeos e os carboidratos. No atual panorama do consumo de produtos cárneos no Brasil, os produtos de origem avícola apresentam significativo aumento, e a elaboração de produtos derivados tem acompanhado este avanço. Neste sentido, identificar se existe misturas cárneas indevidas nos subprodutos é de vital importância. Para a avaliar a qualidade destes, a avaliação da origem e da qualidade das proteínas musculares é um fator de grande importância, assim como a avaliação das perdas proteicas ocorridas no processo de rigor mortis. As principais técnicas para quantificação das proteínas são as eletroforéticas e densitométricas. Para avaliação de suas perdas, pode ser utilizado ainda, a técnica de histologia dos tecidos musculares. Para realização deste trabalho, partiu-se de que as proteínas musculares de frangos e perus apresentam diferentes características estruturais devido à expressão gênica e suas estruturas primárias podem ser identificadas mesmo em misturas, por técnicas eletroforéticas e, através da densitometria, quantificadas. Foram colhidos fragmentos de músculo peitoral de aves de cada espécie abatidas em laboratórios, para além da avaliação da mistura de extratos proteicos, realizar a avaliação das perdas proteicas ocorridas durante a resolução do rigor mortis. Os fragmentos obtidos foram avaliados em técnicas histológicas e eletroforéticas, tendo sido coletados em tempos correntes de 0, 30, 60, 90, 120 e 150 minutos após o abate. Ainda foi realizada a extração com outra parte dos mesmos fragmentos por maceração e centrifugação, e posterior mistura de extratos na proporção 80, 60, 40 e 20%, para posterior submissão a...
Comparison between mixtures of protein extracts in poultry with commercial interests
Keywords: Eletroforese em gel; Musculos - Histologia; Frango de corte; Proteinas musculares; Broilers (Chickens); Muscle proteins